CRITICAL THINKING AND READING IN SOCIAL SCIENCES (Revista Electrónica Calidad en la Educación Superior, 2017)
The appreciation of reading as a social activity, has positioned itself as one of the ways to foster the development of thought and especially a critical and reflective thinking (Lipman, 1998). Hence the purpose of this article is to make a dissertation about the cognitive competences and skills that the reader of the social sciences should handle in the 21st century when addressing their own gender area (Cassany, 2004). Therefore, the reader is expected to assume a critical position, a responsible and autonomous conscious attitude like conditions that authorize him to question the knowledge and thus to construct one own voice that reflects his self-critical commitment to knowledge and against the transformation of social reality (Sanmarti, 2011).